India : Synthesis Study of Public Financial Management and Accountability in Urban Local Bodies - World Bank (Washington, DC, 2012)
This study assesses the current state of Public Financial Management and Accountability (PFMA) systems in Indian urban local bodies. It identifies, analyzes, and documents good practices, focusing on their existing context, success factors, and replicability. It is important to mention that urban governance in India is a state subject and there are vast differences in the levels of reform that have achieved in different states. For the purpose of comparison, this study has developed good practice benchmarks in each PFMA area and used those to compare practices across Urban Local body (ULB)s. The study analyzes linkages between the legislative, budgeting, implementation, reporting, and oversight process in urban local bodies. Benchmarks and indicators have been developed for each strategic area. Analysis of policy, practice, and progress in each strategic area has also been conducted. This study synthesizes existing literature on PFMA in urban local bodies, identifies key PFMA areas where focused attention was required, and suggests ways forward. The main objectives are: 1) To describe the current PFMA environment in urban local bodies in India and identify replicable good practices; 2) To use the Public Expenditure and Financial Accountability (PEFA) benchmarks in developing good practice in each PFMA activity and to develop indicators for assessing PFMA in Indian urban local bodies; 3) To identify challenges and suggest priorities for improving the PFMA environment in Indian urban local bodies so as to feed into Jawaharlal Nehru National Urban Renewal Mission (JNNURM). This study does not focus on the financial performance or on quality of expenditure in terms of specific aspects of efficiency or effectiveness of spending by urban local bodies. It does not cover intergovernmental relations either in any level of detail except to the extent that such relations impact PFMA performance. It is important to mention that this study does not attempt to develop a scoring system for indicators and therefore does not rate relative performance among urban local bodies. It does however suggest as a key recommendation that states could adopt a scoring system or a "PFMA Report Card" for the urban local bodies as a means of comparison of PFMA performance to build a demand for better governed ULBs.